Edubridge: Connecting Intramuros Universities Students with professional statisticians in Manila. - De Jesus, Margarita C., Demafeliz, John Cris A., Dinglasan, Ella F., Lozano, Evnney Rome, J., Tado, May Jean D., Torres, Katrina Ysabelle. T. November 2024. 4 0 16; 5 (2024)
Also, fosters lifelong education, collaboration and develops critical skills necessary to education and career. EduBridge builds an educated and empowered society, advancing social and economic growth.
Feasibility Study: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2